catalyst
By using the catalyst structure of the Ta layer and Pt layer in PEMFC, the problems of high cost and active degradation of platinum electrocatalysts are solved, the mass activity and surface area of the catalyst are improved, the life of the fuel cell is extended and the cost is reduced.
Patent Information
- Application Number
- CN201980025552.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-04-13
- Filing Date
- 2019-04-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2039-04-11
AI Technical Summary
The high cost of platinum electrocatalysts and catalyst activity degradation problems in existing polymer electrolyte membrane fuel cells (PEMFCs) lead to degradation of device performance and shortening of life.
The Ta layer and a catalyst structure containing the Pt layer are prepared by deposition techniques such as sputtering, atomic layer deposition, etc. The average thickness of the -Ta layer is between 0.04 nanometers and 30 nanometers, and the average thickness of the Pt layer is between 0.04 nanometers and 50 nanometers. The atomic ratio of Pt and Ta is in the range of 0.01:1 to 10:1, increasing the catalyst surface area ratio and improving fuel cell performance.
The mass activity and specific surface area of the oxygen reduction reaction (ORR) electrocatalyst is significantly improved, extending the service life of the fuel cell and reducing costs.
Smart Images

Figure CN112042023B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Patent Application No. 62 / 657,189, filed April 13, 2018, the disclosure of which is incorporated herein by reference in its entirety.
[0003] This invention was made with Government support awarded by DOE under Contract No. DE-EE0007270. The Government has certain rights in this invention. Background Art
[0004] Fuel cells generate electricity through electrochemical oxidation of a fuel and reduction of an oxidant. Fuel cells are generally classified according to the type of electrolyte and the type of fuel and oxidant reactants. One type of fuel cell is a polymer electrolyte membrane fuel cell (PEMFC), in which the electrolyte is a polymer ion conductor and the reactants are hydrogen fuel and oxygen as an oxidant. Oxygen is generally provided by ambient air.
[0005] PEMFC generally requires the use of electrocatalysts to increase the reaction rates of hydrogen oxidation reaction (HOR) and oxygen reduction reaction (ORR), which improves PEMFC performance. PEMFC electrocatalysts generally contain platinum, a relatively expensive precious metal. It is generally desirable to minimize the platinum content in PEMFC, thereby increasing the catalyst activity (specific activity) per unit catalyst surface area and increasing the catalyst surface area (specific surface area or specific area) per catalyst mass. HOR and ORR occur on the catalyst surface, so increasing the specific surface area and / or specific activity can reduce the device to minimize cost. However, sufficient platinum content is required to provide sufficient catalytic activity and PEMFC device performance. Therefore, it is necessary to improve the catalyst activity (mass activity) per unit catalyst mass. There are two general methods for improving mass activity, that is, the amount of catalyst required to achieve the desired absolute performance, thereby reducing costs.
[0006] To maximize specific area, PEMFC electrocatalysts are typically present in the form of nanoscale thin films or particles on a support material. An exemplary support material for nanoparticle PEMFC electrocatalysts is carbon black, and an exemplary support material for thin film electrocatalysts is whiskers.
[0007] To increase specific activity, PEMFC Pt ORR electrocatalysts generally also contain certain transition metals such as cobalt or nickel. Without being bound by theory, it is believed that the incorporation of certain transition metals into the Pt lattice causes the contraction of Pt atoms on the catalyst surface, which increases the kinetic reaction rate by changing the molecular oxygen binding and dissociation energies and the binding energies of reaction intermediates and / or observed species.
[0008] PEMFC electrocatalysts can be doped with other precious metals. For example, HOR PEMFC Pt electrocatalysts can be alloyed with ruthenium to improve tolerance to carbon monoxide (a known Pt catalyst poison). HOR and ORR PEMFC electrocatalysts can also be doped with iridium to promote the activity of oxygen evolution reaction (OER). In the absence of fuel and during the startup and shutdown of the PEMFC system, the improved OER activity can improve the durability of PEMFC under unintentional operation. However, the incorporation of iridium into PEMFCCORR electrocatalysts can lead to reduced mass activity and increased catalyst costs. Iridium has a lower specific activity than platinum for ORR, which may lead to reduced catalyst mass activity. Iridium is also a precious metal, so its incorporation can increase costs. PEMFC Pt electrocatalysts can also be doped with gold, which is also a precious metal and can increase costs. It is known that gold is relatively inactive for HOR and ORR in acidic electrolytes. Since gold tends to be preferentially separated to the surface of the electrocatalyst, the incorporation of gold can lead to significant deactivation of HOR and ORR, thereby preventing active catalytic sites.
[0009] PEMFC electrocatalysts may have different structures and compositional forms. The structures and compositional forms are usually adjusted by specific processing methods during electrocatalyst manufacture, such as changes in electrocatalyst deposition methods and annealing methods. PEMFC electrocatalysts may be uniform in composition, layered in composition, or may contain a composition gradient throughout the electrocatalyst. Adjusting the composition distribution within the electrocatalyst may improve the activity and durability of the electrocatalyst. PEMFC electrocatalyst particles or nanoscale films may have a substantially smooth surface or may have atomic or nanoscale roughness. PEMFC electrocatalysts may be uniform in structure or may be nanoporous, consisting of nanoscale pores and solid catalyst ligaments.
[0010] In a PEMFC device, electrocatalysts may lose performance over time due to various degradation mechanisms, which induce structural changes and composition changes. Such performance losses may shorten the practical life of such systems. For example, electrocatalyst degradation may occur due to loss of electrocatalyst activity per unit surface area and loss of electrocatalyst surface area. For example, electrocatalyst specific activity may be lost due to dissolution of electrocatalyst alloying elements. Nanoparticles and nanoscale thin film electrocatalysts may lose surface area, for example due to loss of Pt dissolution, particle sintering, agglomeration, and surface roughness.
[0011] There is a need for additional electrocatalysts and systems containing such catalysts, including those that address one or more of the problems discussed above. Summary of the invention
[0012] In one aspect, the present disclosure provides a catalyst comprising a Ta layer having an outer layer having a layer comprising Pt directly thereon, wherein the Ta layer has an average thickness in a range of 0.04 nm to 30 nm (in some embodiments, in a range of 0.04 nm to 20 nm, 0.05 nm to 20 nm, 0.05 nm to 10 nm, 0.05 nm to 8 nm, 0.05 nm to 6 nm, 0.05 nm to 5 nm, 0.05 nm to 4 nm, 0.05 nm to 3 nm, 0.05 nm to 2 nm, or even 0.35 nm to 1.44), wherein the layer comprising Pt has an average thickness in a range of 0.04 nm to 50 nm (in some embodiments, in a range of 0.04 nm to 40 nm, 0.04 nm to 30 nm, 0.04 nm to 20 nm, 0.04 nm to 10 nm, 0.04 nm to 5 nm, 0.04 nm to 4 nm, 0.17 nm to 1.44 nm, 0.17 nm to 3.67 nm, 0.17 nm to 2.99 nm, 0.17 nm to 2.60 nm, 0.17 nm to 2.20 nm, 0.17 nm to 1.67 nm, 0.17 nm to 1.47 nm, 0.17 nm to 1.33 nm, 0.17 nm to 1.17 nm, 0.17 nm to 0.82 nm, 0.17 nm to 0.73 nm, 0.17 nm to 0.67 nm, 0.17 nm to 0.50 nm, 0. In some embodiments, the catalyst surface area is at least 5% greater (in some embodiments, at least 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or even at least 49%) than the catalyst surface area that would be present in the absence of the Ta layer.
[0013] In another aspect, the present disclosure provides a method for preparing the catalyst described herein, the method comprising depositing any of the layers via a deposition technique independently selected from sputtering (including reactive sputtering), atomic layer deposition, metal organic chemical vapor deposition, molecular beam epitaxy, ion soft landing, thermal physical vapor deposition, electrospray ionization vacuum deposition, and pulsed laser deposition. In some embodiments, the method further comprises annealing at least one of the layers.
[0014] In another aspect, the present disclosure provides an article comprising a nanostructured element comprising a microstructured whisker having an outer surface having a catalyst as described herein thereon. In some embodiments of the article, the first layer is directly on the microstructured whisker.
[0015] In another aspect, the present disclosure provides a method of preparing an article as described herein, the method comprising depositing any of the layers on a microstructured whisker via a deposition technique independently selected from sputtering (including reactive sputtering), atomic layer deposition, metal organic chemical vapor deposition, molecular beam epitaxy, ion soft landing, thermal physical vapor deposition, electrospray ionization vacuum deposition, and pulsed laser deposition. In some embodiments, the method further comprises annealing at least one of the layers.
[0016] In another aspect, the present disclosure provides a method for preparing a catalyst described herein, the method comprising electrochemically cycling the catalyst.
[0017] Surprisingly, the incorporation of a Ta layer underneath the ORR electrocatalyst layer can lead to increased mass activity, specific surface area, and fuel cell performance of the ORR electrocatalyst.
[0018] The catalysts described herein may be used, for example, in fuel cell membrane electrode assemblies. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a side view of an exemplary catalyst described herein.
[0020] Figure 2 is a diagram of an exemplary fuel cell.
[0021] Figure 3 is a graph of electrocatalyst mass activity normalized to platinum group metal content as a function of catalyst loading for the catalysts of Examples 1 to 11 and Comparative Examples A to E.
[0022] Figure 4 is a graph of the electrocatalyst specific activity as a function of catalyst loading for the catalysts of Examples 1 to 11 and Comparative Examples A to E.
[0023] Figure 5 is a graph of electrocatalyst mass activity normalized to platinum group metal content as a function of catalyst loading for the catalysts of Examples 12 to 15 and Comparative Examples A to E.
[0024] Figure 6 is a graph of electrocatalyst specific surface area normalized to platinum group metal content as a function of catalyst loading for the catalysts of Examples 1 to 7, Examples 16 to 18, and Comparative Examples A to E.
[0025] Figure 7 is a graph of the relative oxygen content of the electrocatalyst for Example 2 and Examples 4-8 as a function of the tantalum content of the electrocatalyst.
[0026] Figure 8 is a high angle annular dark field transmission electron micrograph of the catalyst of Example 2 at 1,000,000x magnification after deposition of the catalyst onto optional support whiskers.
[0027] Fig. 9 is a high angle annular dark field transmission electron micrograph of the catalyst of Example 2 at 1,000,000x magnification after annealing the catalyst.
[0028] Fig.10 is a high angle annular dark field transmission electron micrograph of the catalyst of Example 4 at 1,000,000x magnification after deposition of the catalyst onto optional support whiskers.
[0029] Fig.11 is a high angle annular dark field transmission electron micrograph of the catalyst of Example 4 at 1,000,000x magnification after annealing the catalyst.
[0030] Fig.12 is a high angle annular dark field transmission electron micrograph of the catalyst of Example 4 at 1,000,000x magnification after testing the catalyst in a fuel cell.
[0031] Fig.13 is an Energy Dispersive X-ray Spectroscopy elemental map of the platinum and tantalum content of the Example 4 catalyst at 1,500,000x magnification after testing the catalyst in a fuel cell.
[0032] Fig.14 is an Energy Dispersive X-ray Spectroscopy elemental map of the tantalum content of the Example 4 catalyst at 1,500,000x magnification after testing the catalyst in a fuel cell.
[0033] Fig.15 is an Energy Dispersive X-ray Spectroscopy elemental map of the platinum content of the Example 4 catalyst at 1,500,000x magnification after testing the catalyst in a fuel cell.
[0034] Fig.16 are X-ray diffraction spectra of the catalysts of Example 2 and Examples 4 to 8 after deposition of the catalysts onto the optional support whiskers and after annealing the catalysts. DETAILED DESCRIPTION
[0035] In some embodiments, the average thickness of the Ta layer is in the range of 0.04 nm to 30 nm (in some embodiments, in the range of 0.04 nm to 20 nm, 0.05 nm to 20 nm, 0.05 nm to 10 nm, 0.05 nm to 8 nm, 0.05 nm to 6 nm, 0.05 nm to 5 nm, 0.05 nm to 4 nm, 0.05 nm to 3 nm, 00.05 nm to 2 nm, or even 0.35 nm to 1.44 nm). In some embodiments, the average thickness of the layer comprising Pt is between 0.04 nm and 40 nm, 0.04 nm and 30 nm, 0.04 nm and 20 nm, 0.04 nm and 10 nm, 0.04 nm and 5 nm, 0.04 nm and 4 nm, 0.17 nm and 3.67 nm, 0.17 nm and 2.99 nm, 0.17 nm and 2.60 nm, 0.17 nm and 2.20 nm, 0.17 nm and 1.67 nm. , 0.17 nm to 0.82 nm, 0.17 nm to 0.73 nm, 0.17 nm to 0.67 nm, 0.17 nm to 0.50 nm, 0.17 nm to 0.33 nm, 0.50 nm to 2.60 nm, 1.17 nm to 1.67 nm, or even 0.73 nm to 3.67 nm.
[0036] In some embodiments, the catalyst surface area is at least 5% greater (in some embodiments, at least 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 20, 25, 30, 35, 40, 45, or even at least 49%) than the catalyst surface area that would exist in the absence of the Ta layer.
[0037] In some embodiments, the layer comprising Pt comprises Pt grains having a FCC lattice constant in the range of 0.395 nm to 0.392 nm. In some embodiments, the layer comprising Pt comprises Pt grains having a grain size in the range of 2 nm to 20 nm (in some embodiments, in the range of 5 nm to 10 nm or even 5 nm to 9.3 nm).
[0038] In some embodiments, the catalyst material further comprises at least one pair of alternating layers, wherein the first alternating layers comprise Ta, and wherein the second alternating layers comprise Pt.
[0039] In some embodiments, the catalyst further comprises nanoscale metal grains extending from the surface of the catalyst. In some embodiments, the surface metal grains comprise at least 10 atomic % (in some embodiments, at least 15 atomic %, 20 atomic %, 25 atomic %, 30 atomic %, 40 atomic %, 50 atomic %, 60 atomic %, 70 atomic %, 75 atomic %, 80 atomic %, 90 atomic %, 95 atomic %, 98 atomic %, 99 atomic %, or even at least 99.9 atomic %) of Ir. In some embodiments, the length of the surface metal grains is in the range of 0.25 nm to 10 nm (in some embodiments, in the range of 0.25 nm to 8 nm, 0.25 nm to 6 nm, 0.25 nm to 4 nm, 0.25 nm to 3 nm, 0.25 nm to 2 nm, 0.25 nm to 1 nm, 1 nm to 10 nm, 1 nm to 8 nm, 1 nm to 6 nm, 1 nm to 4 nm, 1 nm to 3 nm, or even in the range of 1 nm to 2 nm). In some embodiments, the length of the surface metal grains is less than 8 nanometers (in some embodiments, less than 7 nanometers, 6 nanometers, 5 nanometers, 4 nanometers, 3 nanometers, 2 nanometers, or even less than 1 nanometer). In some embodiments, the diameter of the surface metal grains is in the range of 0.25 nanometers to 5 nanometers (in some embodiments, in the range of 0.25 nanometers to 4 nanometers, 0.25 nanometers to 3 nanometers, 0.25 nanometers to 2 nanometers, 0.25 nanometers to 1 nanometer, 1 nanometer to 5 nanometers, 1 nanometer to 4 nanometers, 1 nanometer to 3 nanometers, or even 1 nanometer to 2 nanometers). In some embodiments, the diameter of the surface metal grains is less than 5 nanometers (in some embodiments, less than 4 nanometers, 3 nanometers, 2 nanometers, or even less than 1 nanometer).
[0040] In some embodiments, an Ir layer is present between the Ta layer and the Pt layer, and the average thickness of the layer comprising Ir on the microstructured whiskers is in the range of 0.04 nm to 50 nm (in some embodiments, in the range of 0.04 nm to 40 nm, 0.04 nm to 30 nm, 0.04 nm to 20 nm, 0.04 nm to 10 nm, 0.04 nm to 5 nm, 0.04 nm to 4 nm, 0.04 nm to 3 nm, 0.04 nm to 2 nm, 0.04 nm to 1 nm, 0.04 nm to 0.63 nm, 0.04 nm to 0.32 nm, 0.04 nm to 0.16 nm, or even 0.16 nm to 0.63 nm). In some embodiments, the atomic ratio of Ta to Ir is in the range of 0.01:1 to 100:1 (in some embodiments, in the range of 0.1:1 to 9:1, 0.33:1 to 3:1, 0.5:1 to 2:1, or even 0.59:1 to 2.35:1).
[0041] In some embodiments, the layer comprising Pt further comprises Ni. In some embodiments, the atomic ratio of Pt to Ni is in the range of 0.5:1 to 5:1 (in some embodiments, in the range of 0.5:1 to 2:1, 0.5:1 to 1:1, 0.57:1 to 0.69:1, or even 0.60:1).
[0042] In some embodiments, the catalyst material comprises a nanostructured element comprising a microstructured whisker having an outer surface having a Ta layer thereon, the Ta layer having an outer layer having a layer comprising Pt directly thereon. In some embodiments, the Ta layer is directly on the microstructured whisker. In some embodiments, the catalyst material further comprises at least one pair of alternating layers disposed between the outer surface of the microstructured whisker and the layer comprising Ta, wherein the first alternating layer comprises Ta and is directly on the microstructured whisker, and wherein the second alternating layer comprises Pt.
[0043] See also Figure 1 , the exemplary catalyst 99 described herein includes a Ta layer 110 having an outer layer 115, the outer layer having a layer 120 containing Pt directly thereon (i.e., directly on the outer layer 115). The average thickness of the Ta layer 110 on the microstructured whiskers is in the range of 0.04 nanometers to 30 nanometers. The average thickness of the layer 120 containing Pt on the microstructured whiskers 101 is in the range of 0.04 nanometers to 50 nanometers. Pt and Ta are present in an atomic ratio in the range of 0.01:1 to 10:1. As shown, the optional nanostructured element 100 includes a microstructured whisker 101 having an outer surface 105, the outer surface having a Ta layer 110 located thereon (i.e., located on the outer surface 105).
[0044] In some embodiments, the microstructured whiskers are attached to a backing (eg, a film). In some embodiments, the backing has microstructures on at least one of its surfaces.
[0045] Suitable whiskers can be provided by techniques known in the art, including those described in U.S. Pat. Nos. 4,812,352 (Debe), 5,039,561 (Debe), 5,338,430 (Parsonage et al.), 6,136,412 (Spiewak et al.), and 7,419,741 (Vernstrom et al.), the disclosures of which are incorporated herein by reference. Generally, microstructured whiskers can be provided by, for example, vacuum depositing (e.g., by sublimation) a layer of organic or inorganic material on a substrate (e.g., a microstructured catalyst transfer polymer sheet), and then, in the case of perylene red deposition, converting the perylene red pigment into microstructured whiskers by thermal annealing. Typically, the vacuum deposition step is performed at or below about 10-3 The exemplary microstructures were prepared by thermal sublimation and vacuum annealing of an organic pigment, CI Pigment Red 149 (ie, N,N'-di(3,5-dimethylphenyl)perylene-3,4:9,10-bis(dicarboximide)). Methods for preparing organic microstructured layers are reported, for example, in Materials Science and Engineering, Vol. A158, (1992), pp. 1-6; J. Vac. Sci. Technol. A, 5(4), July / August 1987, pp. 1914-1916; J. Vac. Sci. Technol. A, 6, (3), May / August 1988, pp. 1907-1911; "Thin Solid Films", Vol. 186, 1990, pp. 327-47; J. Mat. Science Magazine, 25, 1990, pp. 5257-68; "Rapidly Quenched Metals", Proc. of the Fifth International Conference on Rapidly Quenched Metals, Würzburg, Germany Int. Conf. on Rapidly Quenched Metals, Wurzburg, Germany) (September 3-7, 1984), edited by S. Steeb et al., Elsevier Science Publishers BV, New York (1985), pp. 1117-1124; Photo. "Sci. and Eng. (Materials Science and Engineering)", 24, (4), July / August 1980, pp. 211-216; and in U.S. Patent Applications 4340276 (Maffitt et al.) and 4568598 (Bilkadi et al.), the disclosures of which are incorporated herein by reference. The properties of catalyst layers using carbon nanotube arrays are reported in the paper "High Dispersion and Electrocatalytic Properties of Platinum on Well-Aligned Carbon Nanotube Arrays," Carbon, 2004, Vol. 42, pp. 191-197. The properties of catalyst layers using fusilli or wooly silica are reported, for example, in U.S. Patent Application Publication No. 2004 / 0048466A1 (Gore et al.).
[0046] Vacuum deposition can be performed in any suitable apparatus (see, e.g., U.S. Patent Applications 5,338,430 (Parsonage et al.), 5,879,827 (Debe et al.), 5,879,828 (Debe et al.), 6,040,077 (Debe et al.), and 6,319,293 (Debe et al.), and U.S. Patent Application 2002 / 0004453A1 (Haugen et al.), the disclosures of which are incorporated herein by reference). An exemplary apparatus is schematically shown in U.S. Patent 5,338,430 (Parsonage et al.). Figure 4 A, and discussed in the accompanying text, wherein a substrate is mounted on a drum which is then rotated over a sublimation or evaporation source for deposition of an organic precursor (eg, perylene red pigment) which is then annealed to form whiskers.
[0047] Typically, the nominal thickness of the deposited perylene red pigment is in the range of about 50 nm to 500 nm. Typically, the average cross-sectional size of the whiskers is in the range of 20 nm to 60 nm, the average length is in the range of 0.3 microns to 3 microns, and the areal number density is in the range of 30 whiskers / square micron to 70 whiskers / square micron.
[0048] In some embodiments, the whiskers are attached to a backing. Exemplary backings include polyimide, nylon, metal foil, or other materials capable of withstanding thermal annealing temperatures up to 300° C. In some embodiments, the average thickness of the backing is in the range of 25 microns to 125 microns.
[0049] In some embodiments, the backing has a microstructure on at least one upper surface of its surface. In some embodiments, the microstructure is composed of feature structures of substantially uniform shape and size, which are at least three times (in some embodiments, at least four times, five times, ten times or more) the average size of the whiskers. The shape of the microstructure may be, for example, a V-shaped groove and peak (see, for example, U.S. Pat. No. 6,136,412 (Spawk et al.), the disclosure of which is incorporated herein by reference) or a cone (see, for example, U.S. Pat. No. 7,901,829 (Debbie et al.), the disclosure of which is incorporated herein by reference). In some embodiments, some portions of the microstructure features extend in a periodic manner over an average or majority of microstructured peaks, such as every 31st V-groove peak being 25% or 50% or even 100% higher than the V-groove peak on either side thereof. In some embodiments, the portion of the feature structure extending over a majority of microstructured peaks may be at most 10% (in some embodiments, at most 3%, 2% or even at most 1%). In a roll-to-roll coating operation, when the coated substrate moves on the surface of the roller, the use of occasionally higher microstructural features can be beneficial to protect the uniformly smaller microstructural peaks. Occasionally, the higher feature portion contacts the surface of the roller without contacting the peak of the smaller microstructure, so as the substrate moves during the coating process, very little microstructural material or whisker material may be scratched or otherwise damaged. In some embodiments, the microstructural features are substantially less than half the thickness of the membrane, wherein when the membrane electrode assembly is prepared, the catalyst will be transferred to the membrane. This makes it impossible for the higher microstructural features to penetrate through the membrane during the catalyst transfer process, wherein the higher microstructural features can be stacked on the opposite side of the membrane. In some embodiments, the highest microstructural features are less than 1 / 3 or 1 / 4 of the membrane thickness. For the thinnest ion exchange membrane (e.g., a thickness of about 10 microns to 15 microns), it may be advantageous to have a substrate with a microstructural feature with a height not greater than about 3 microns to 4.5 microns. In some embodiments, the steepness of the sides of the V-shaped or other microstructured features or the angles included between adjacent features are expected to be approximately 90° to facilitate catalyst transfer during the lamination transfer process and to increase the surface area of the electrode since the surface area of the microstructured layer is the square root of two (1.414) times the planar geometric surface of the base backing.
[0050] Generally speaking, catalyst can be deposited by technology known in the art. Exemplary deposition techniques include those independently selected from the following: sputtering (including reactive sputtering), atomic layer deposition, metal organic chemical vapor deposition, molecular beam epitaxy, thermal physical vapor deposition, electrospray ionization vacuum deposition and pulsed laser deposition. Other general details can be found in, for example, U.S. Patents 5879827 (Debe et al.), 6040077 (Debe et al.) and 7419741 (Vernstrom et al.), the disclosures of which are incorporated herein by reference. Thermal physical vapor deposition methods use suitable high temperatures (for example, by resistance heating, electron beam guns or lasers) to melt or sublimate the target (source material) into a gaseous state, which then passes through a vacuum space and then condenses the gasified form onto the substrate surface. Thermal physical vapor deposition equipment is known in the art, including, for example, metal evaporators or organic molecular evaporators available from CreaPhys GmbH, Dresden, Germany, under the trade names "METAL Evaporator (ME Series)" or "ORGANIC MOLECULAR EVAPORATOR (DE Series)", respectively; another example of an organic material evaporator is available from Mantis Deposition LTD, Oxfordshire, UK, under the trade name "ORGANIC MATERIAL SEVAPORATIOR (ORMA Series)". The catalyst material comprising multiple alternating layers can be sputtered, for example, from multiple targets (e.g., Pt is sputtered from a first target, Ni is sputtered from a second target, Ta is sputtered from a third target, and Ir (if present) is sputtered from a fourth target, or from a target comprising more than one element (e.g., Pt and Ni)). It is desirable that the coating is applied to the gas distribution layer, gas dispersion layer, catalyst transfer layer or membrane in a single step so that the heat of condensation of the catalyst coating sufficiently heats the catalyst or carrier Pt, Ni or Ta atoms (if applicable) and substrate surface below, thereby providing sufficient surface mobility so that atoms are well mixed and form thermodynamically stable alloy domains. In some embodiments, it is desirable to keep the catalyst as a different layer, and the deposition conditions can be adjusted to minimize the mixing of atoms. Alternatively, for example, a high temperature or heated substrate can also be provided to promote the atomic mobility, or a low temperature or cooled substrate can be provided to reduce atomic mobility. In some embodiments, sputtering is performed at least partially in an atmosphere comprising argon. Catalysts in the form of organometallics can be deposited, for example, by soft landing or reactive landing techniques of mass-selected ions. Soft landing of mass-selected ions is used to transfer catalytically active metal complexes together with organic ligands from the gas phase to an inert surface. This method can be used to prepare materials with defined active sites, thereby achieving highly controlled molecular design for surfaces under ambient or conventional vacuum conditions.Additional details can be found, for example, in Johnson et al., Chem., 2010, 82, pp. 5718-5727, and Johnson et al., Chemistry: A European Journal, 2010, vol. 16, pp. 14433-14438, the disclosures of which are incorporated herein by reference.
[0051] The planar equivalent thickness of a single deposited catalyst layer is the thickness if deposited on a substantially flat planar substrate. The planar equivalent thickness may depend on, for example, the area catalyst loading and catalyst density of the layer. For example, the deposited Pt / cm 2 The surface area is 10 μg and the density is 21.45 g / cm 3 The plane equivalent thickness of the single-layer Pt is calculated to be 4.7 nm, and the Ni layer with the same area loading (8.90 g / cm 3 ) has a thickness of 11.2 nm and has a Ta layer with the same area loading (16.4 g / cm 3 One or more layers may be deposited to obtain a catalyst material having a total planar equivalent thickness equal to the sum of the planar equivalent thicknesses of each constituent layer.
[0052] In some embodiments, the thickness of the catalyst material is the planar equivalent thickness of the catalyst material divided by the combined surface area of the whiskers and the backing. For example, the combined surface area is 10 cm 2 Surface area / cm 2 A planar equivalent thickness of 20 nm of catalyst material deposited onto a planar backing surface including microstructured whiskers will result in a catalyst thickness of 2 nm on the whiskers. The surface area of the whiskers depends on the whisker cross-sectional dimensions, whisker length, and whisker areal density (number of whiskers per unit area of backing). In some embodiments, the surface area of the whiskers is between 1 and 100 cm 2 / cm 2 The surface area of the backing is within the range (in some embodiments, within 2 cm 2 / cm 2 Up to 50cm 2 / cm 2 , 5cm 2 / cm 2 Up to 25cm 2 / cm 2 or even 5cm 2 / cm 2 Up to 15cm 2 / cm 2 In some embodiments, the surface area of the backing may be within the range of 1 cm 2 / cm2 Up to 10cm 2 / cm 2 The planar backing area is within the range (in some embodiments, within 1 cm 2 / cm 2 Up to 5cm 2 / cm 2 within the range of 1cm 2 / cm 2 Up to 2cm 2 / cm 2 The combined surface area of the whiskers and the backing is the product of the whisker surface area and the backing surface area. For example, a surface area of 1.5 cm 2 Surface area / cm 2 The surface area of the backing is 10 cm 2 / cm 2 The whiskers of the backing area will produce 15cm 2 Combined surface area / cm 2 The combined surface area of the planar backing area.
[0053] In some embodiments, the method for preparing the catalyst material of this article includes annealing the catalyst. Generally speaking, annealing can be completed by techniques known in the art, including heating the catalyst material by, for example, in an oven or a heating furnace, with a laser and with infrared technology. Annealing can be carried out in, for example, an inert or reactive gas environment. Although not wanting to be limited by theory, it is believed that annealing can cause structural changes on the atomic scale, which can affect the activity and durability of the catalyst. In addition, it is believed that annealing can induce mobility in the atomic composition of nano-scale particles and films, which can lead to the growth of particles or film grains. In the case of multi-element mixtures, alloys or layered particles and films, it is believed that annealing can induce, for example, separation of components in particles or films to the surface, forming random, disordered alloys, and forming ordered intermetallic compounds, depending on the component element properties and annealing environment. For additional details on annealing, see, for example, van der Vliet et al., Nature Materials, 2012, 11, pp. 1051-1058; Wang et al., Nature Materials, 2013, 12, pp. 81-87, and U.S. Pat. No. 8,748,330 B2 (Debe et al.), the disclosures of which are incorporated herein by reference.
[0054] In some embodiments, the catalyst is substantially non-porous (i.e., the catalyst includes spherical and / or non-spherical void volumes, wherein at least 75% of the void volume is contained within the catalyst film (in some embodiments, at least 85%, 90%, 95%, 99% or even 100% is contained within the catalyst film), and wherein the average diameter of the void volume is less than 1 nm (in some embodiments, less than 0.8 nm, 0.6 nm, 0.4 nm, 0.2 nm or even 0.01 nm)).
[0055] In some embodiments, the method for preparing the catalyst described herein comprises depositing any of the layers via a deposition technique independently selected from sputtering (including reactive sputtering), atomic layer deposition, metal organic chemical vapor deposition, molecular beam epitaxy, ion soft landing, thermal physical vapor deposition, electrospray ionization vacuum deposition, and pulsed laser deposition. In some embodiments, the method for preparing the catalyst described herein comprises annealing at least one of the layers.
[0056] In some embodiments, the method for preparing the catalyst described herein includes electrochemically cycling the catalyst. In some embodiments, the method for preparing the catalyst described herein includes cycling the catalyst in an acidic electrolyte. In some embodiments, the method for preparing the catalyst described herein includes cycling the catalyst between 0.60V and 1.00V relative to the potential of a standard hydrogen electrode. Such techniques are well known in the art (see also, for example, a co-pending application with U.S. serial number 62 / 657184 filed on April 13, 2018), the disclosure of which is incorporated herein by reference.
[0057] In some embodiments, the microstructured whiskers are attached to a backing (eg, a film). In some embodiments, the backing has microstructures on at least one of its surfaces.
[0058] The catalysts described herein can be used, for example, in a fuel cell membrane electrode assembly (MEA). "Membrane electrode assembly" refers to a layered interlayer of fuel cell materials including a membrane, an anode electrode layer, and a cathode electrode layer, and a gas diffusion layer. Typically, the cathode catalyst layer comprises the catalyst described herein, but in some embodiments, the anode catalyst layer independently comprises the catalyst described herein.
[0059] In some embodiments, the article comprises a catalyst described herein. In some embodiments, the article does not comprise a conductive carbon-based material.
[0060] The MEA includes, in order:
[0061] a first gas distribution layer having first and second opposing major surfaces;
[0062] an anode catalyst layer having a first major surface and a second major surface opposite to each other, the anode catalyst comprising a first catalyst;
[0063] Electrolyte membrane;
[0064] a cathode catalyst layer having a first major surface and a second major surface that are opposite to each other, the cathode catalyst layer comprising a second catalyst; and
[0065] a second gas distribution layer having first and second opposite major surfaces,
[0066] The electrolyte membrane conducts the reaction intermediate ions between the anode catalyst layer and the cathode catalyst layer. The electrolyte membrane preferably has high durability in an electrochemical environment, including chemical and electrochemical oxidation stability. The electrolyte membrane preferably has low ionic resistance for the transmission of reaction intermediate ions, but is a relatively impermeable barrier to other ions, electrons and reaction substances. In some embodiments, the electrolyte membrane is a proton exchange membrane (PEM), which conducts cations. In a PEM fuel cell, the electrolyte membrane preferably conducts protons. PEM is generally a partially fluorinated or perfluorinated polymer consisting of a structural backbone and a cation exchange side group, and PEM is purchased from EIduPont de Nemours and Company, Wilmington, Delaware under the trade name "NAFION"; purchased from Solvay in Brussels, Belgium under the trade name "AQUIVION"; purchased from 3M Company in St. Paul, Minnesota under the trade name "3M PFSA MEMBRANE"; and purchased from Asahi Glass Co. in Tokyo, Japan under the trade name "FLEMION".
[0067] The gas distribution layer generally delivers gas uniformly to the electrodes, and in some embodiments the gas distribution layer is conductive. In the case of a fuel cell, it also has the effect of removing water in the form of vapor or liquid. The gas distribution layer is typically porous to allow reactants and products to be transported between the electrodes and the flow field. The source of the gas distribution layer includes carbon fibers randomly oriented to form a porous layer, in the form of a nonwoven paper or woven fabric. Nonwoven carbon paper, for example, is available from Mitsubishi Rayon Co., Ltd. in Tokyo, Japan, under the trade name "GRAFIL U-105"; from Toray Corp. in Tokyo, Japan, under the trade name "TORAY"; from AvCarb Material Solutions in Lowell, Massachusetts, under the trade name "AVCARB"; from SGL Group, the Carbon Company in Wiesbaden, Germany, under the trade name "SIGRACET"; from Freudenberg FCCT SE & Co. KG, Fuel Cell Component Technologies in Weinheim, Germany, under the trade name "Freudenberg"; and from Engineered Fibers Technology (EFT) in Shelton, Connecticut, under the trade name "SPECTRACARB GDL." Woven carbon fabrics or cloths are available, for example, from ElectroChem Inc., Woburn, MA, under the trade designations "EC-CC1-060" and "EC-AC-CLOTH"; from NuVant Systems Inc., Crown Point, Indiana, under the trade designations "ELAT-LT" and "ELAT"; from BASF Fuel Cell GmbH, North America, under the trade designation "E-TEK ELAT LT"; and from Zoltek Corp., St. Louis, Missouri, under the trade designation "ZOLTEK CARBON CLOTH." The nonwoven paper or woven fabric may be treated to alter its hydrophobicity (e.g., by treatment with a polytetrafluoroethylene (PTFE) suspension followed by drying and annealing). The gas dispersion layer typically includes a porous layer of submicron electronically conductive particles (e.g., carbon) and a binder (e.g., PTFE). While not wanting to be limited by theory, it is believed that the gas dispersion layer facilitates reactant and product water transport between the electrode and the gas distribution layer.
[0068] At least one of the anode or cathode catalysts is a catalyst as described herein, i.e., a catalyst comprising a Ta layer having an outer layer having a layer comprising Pt directly thereon, wherein the Ta layer has an average thickness in a range of 0.04 nm to 30 nm (in some embodiments, in a range of 0.04 nm to 20 nm, 0.05 nm to 20 nm, 0.05 nm to 10 nm, 0.05 nm to 8 nm, 0.05 nm to 6 nm, 0.05 nm to 5 nm, 0.05 nm to 4 nm, 0.05 nm to 3 nm, 0.05 nm to 2 nm, or even 0.35 nm to 1.44), wherein the layer comprising Pt has an average thickness in a range of 0.04 nm to 50 nm (in some embodiments, in a range of 0.04 nm to 40 nm, 0.04 nm to 30 nm, 0.04 nm to 20 nm, 0.04 nm to 10 nm, 0.04 nm to 5 nm, 0.04 nm to 4 nm, 0.17 nm to 3.67 nm, 0.17 nm to 2.99 nm, 0.17 nm to 2.60 nm, 0.17 nm to 2.20 nm, 0.17 nm to 1.67 nm, 0.17 nm to 1.47 nm, 0.17 nm to 1.33 nm, 0.17 nm to 1.17 nm, 0.17 nm to 0.82 nm, 0.17 nm to 0.73 nm, 0.17 nm to 0.67 nm, 0.17 nm to 0.50 nm In some embodiments, the catalyst surface area is at least 5% greater (in some embodiments, at least 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or even at least 49%) than the catalyst surface area that would be present in the absence of the Ta layer. The "other catalyst layer" can be a conventional catalyst known in the art and provided by techniques known in the art (e.g., U.S. Patents 5,759,944 (Buchanan et al.), 5,068,161 (Keck et al.), and 4,447,506 (Luczak et al.)), the disclosures of which are incorporated herein by reference.
[0069] A fuel cell is an electrochemical device that combines hydrogen fuel and oxygen from the air to generate electricity, heat, and water. A fuel cell does not utilize combustion, and therefore, generates little, if any, hazardous effluent. A fuel cell converts hydrogen fuel and oxygen directly into electrical energy, and operates at much higher efficiencies than, for example, an internal combustion generator.
[0070] Reference Figure 2 , the exemplary fuel cell 200 includes a first gas distribution layer 201 adjacent to an anode 203. Adjacent to the anode 203 is an electrolyte membrane 204. A cathode 205 is located adjacent to the electrolyte membrane 204, and a second gas distribution layer 207 is located adjacent to the cathode 205. In operation, hydrogen fuel is introduced into the anode portion of the fuel cell 200, passing through the first gas distribution layer 201 and being located on the anode 203. At the anode 203, the hydrogen fuel is separated into hydrogen ions (H + ) and electron (e - ).
[0071] The electrolyte membrane 204 allows only hydrogen ions or protons to pass through the electrolyte membrane 204 to the cathode portion of the fuel cell 200. Electrons cannot pass through the electrolyte membrane 204, but flow through an external circuit in the form of an electric current. This current can provide power to an electrical load 217 (such as an electric motor) or be directed to an energy storage device (such as a rechargeable battery).
[0072] Oxygen flows into the cathode side of the fuel cell 200 through the second distribution layer 207. As the oxygen passes through the cathode 205, the oxygen, protons, and electrons combine to generate water and heat.
[0073] Exemplary embodiments
[0074] 1A. A catalyst comprising a Ta layer having an outer layer having a Pt-containing layer directly thereon, wherein the Ta layer has an average thickness in a range of 0.04 nm to 30 nm (in some embodiments, in a range of 0.04 nm to 20 nm, 0.05 nm to 20 nm, 0.05 nm to 10 nm, 0.05 nm to 8 nm, 0.05 nm to 6 nm, 0.05 nm to 5 nm, 0.05 nm to 4 nm, 0.05 nm to 3 nm, 0.05 nm to 2 nm, or even 0.35 nm to 1.44), wherein the Pt-containing layer has an average thickness in a range of 0.04 nm to 50 nm (in some embodiments, in a range of 0.04 nm to 40 nm, 0.04 nm to 30 nm, 0.04 nm to 20 nm, 0.04 nm to 10 nm, 0.04 nm to 5 nm, 0.04 nm to 4 nm, 0.17 nm to 3 .67 nm, 0.17 nm to 2.99 nm, 0.17 nm to 2.60 nm, 0.17 nm to 2.20 nm, 0.17 nm to 1.67 nm, 0.17 nm to 1.47 nm, 0.17 nm to 1.33 nm, 0.17 nm to 1.17 nm, 0.17 nm to 0.82 nm, 0.17 nm to 0.73 nm, 0.17 nm to 0.67 nm, 0.17 nm to 0.50 nm, 0.17 nm 1 to 0.33 nm, 0.50 nm to 2.60 nm, 1.17 nm to 1.67 nm, or even 0.73 nm to 3.67), and wherein the Pt and the Ta are present in an atomic ratio in the range of 0.01:1 to 10:1 (in some embodiments, in the range of 0.28:1 to 9.04:1, 1.74:1 to 9.04:1, 0.98:1 to 1.41:1, or even 1.16:1 to 2.80:1).
[0075] 2A. The catalyst of exemplary embodiment 1A, wherein the catalyst surface area is at least 5% (in some embodiments, at least 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or even at least 49%) greater than the catalyst surface area that would exist in the absence of the Ta layer.
[0076] 3A. The catalyst of example embodiment 1A or 2A, further comprising at least one pair of alternating layers, wherein the first alternating layers comprise Ta, and wherein the second alternating layers comprise Pt.
[0077] 4A. The catalyst of any preceding A exemplary embodiment, wherein an Ir layer is present between the Ta layer and the Pt layer, and wherein the average thickness of the layer comprising Ir is in the range of 0.04 nm to 50 nm (in some embodiments, in the range of 0.04 nm to 40 nm, 0.04 nm to 30 nm, 0.04 nm to 20 nm, 0.04 nm to 10 nm, 0.04 nm to 5 nm, 0.04 nm to 4 nm, 0.04 nm to 3 nm, 0.04 nm to 2 nm, 0.04 nm to 1 nm, 0.04 nm to 0.63 nm, 0.04 nm to 0.32 nm, 0.04 nm to 0.16 nm, or even 0.16 nm to 0.63 nm).
[0078] 5A. The catalyst of Exemplary Embodiment 4A, wherein the atomic ratio of Ta to Ir is in the range of 0.01:1 to 100:1 (in some embodiments, in the range of 0.1:1 to 9:1, 0.33:1 to 3:1, 0.5:1 to 2:1, or even 0.59:1 to 2.35:1).
[0079] 6A. The catalyst according to any of the preceding A exemplary embodiments, wherein the Pt-containing layer comprises Pt crystallites having an FCC lattice constant in the range of 0.395 nm to 0.392 nm.
[0080] 7A. The catalyst according to any of the preceding A exemplary embodiments, wherein the Pt-containing layer comprises Pt grains having a grain size ranging from 2 nm to 20 nm (in some embodiments, from 5 nm to 10 nm or even from 5 nm to 9.3 nm).
[0081] 8A. The catalyst according to any preceding A exemplary embodiment, wherein the layer comprising Pt further comprises Ni.
[0082] 9A. The catalyst of exemplary embodiment 8A, wherein the atomic ratio of Pt to Ni is in the range of 0.5:1 to 5:1 (in some embodiments, in the range of 0.5:1 to 2:1, 0.5:1 to 1:1, 0.57:1 to 0.69:1, or even 0.60:1).
[0083] 1B. A method for preparing a catalyst according to any of the aforementioned A exemplary embodiments, the method comprising depositing any of the layers via a deposition technique independently selected from sputtering (including reactive sputtering), atomic layer deposition, metal organic chemical vapor deposition, molecular beam epitaxy, ion soft landing, thermal physical vapor deposition, electrospray ionization vacuum deposition and pulsed laser deposition.
[0084] 1C. An article comprising nanostructured elements comprising microstructured whiskers having an outer surface having a catalyst according to any of the preceding A exemplary embodiments thereon.
[0085] 2C. The article of example embodiment 1C, wherein the Ta layer is directly on the microstructured whiskers.
[0086] 3C. The article of example embodiment 1C or 2C, further comprising at least one pair of alternating layers disposed between the outer surface of the microstructured whiskers and the layer comprising Ta, wherein the first alternating layer comprises Ta and is directly on the microstructured whiskers, and wherein the second alternating layer comprises Pt.
[0087] 4C. The article of any preceding C exemplary embodiment, wherein the microstructured whiskers are attached to a backing (eg, a film).
[0088] 5C. The article of exemplary embodiment 4C, wherein the backing has a microstructure on at least one of its surfaces.
[0089] 6C. The article of any preceding C exemplary embodiment, wherein the article does not contain an electrically conductive carbon-based material.
[0090] 1D. A method for preparing an article according to any of the aforementioned C exemplary embodiments, the method comprising depositing any of the layers on a microstructured whisker via a deposition technique independently selected from sputtering (including reactive sputtering), atomic layer deposition, metal organic chemical vapor deposition, molecular beam epitaxy, ion soft landing, thermal physical vapor deposition, electrospray ionization vacuum deposition, and pulsed laser deposition.
[0091] 2D. The method of example embodiment 1D, further comprising annealing at least one of the layers.
[0092] 1E. A method for preparing a catalyst according to any of the preceding A exemplary embodiments, the method comprising electrochemically cycling the catalyst.
[0093] 2E. The method of example embodiment 1E, further comprising circulating the catalyst in an acidic electrolyte.
[0094] 3E. The method of example embodiment 1E or 2E further comprising cycling the catalyst within a range of 0.60 V to 1.00 V relative to the potential of a standard hydrogen electrode.
[0095] The following examples further illustrate the advantages and embodiments of the present invention, but the specific materials and amounts thereof mentioned in these examples, as well as other conditions and details, should not be construed as unduly limiting the present invention. Unless otherwise indicated, all parts and percentages are by weight.
[0096] Example
[0097] Preparation Example A
[0098] Microstructured whiskers used as catalyst supports were prepared according to the methods described in U.S. Pat. Nos. 5,338,430 (Parsonage et al.), 4,812,352 (Debe), and 5,039,561 (Debe), also incorporated herein by reference, using a microstructured catalyst transfer substrate (or MCTS) described in U.S. Pat. No. 6,136,412 (Spiewak et al.), incorporated herein by reference, as a substrate. Perylene red pigment (i.e., N,N'-di(3,5-dimethylphenyl)perylene-3,4:9,10-bis(dicarboximide)) Pigment Red 149, also referred to as "PR149", available from Clariant, Charlotte, NC) was sublimation vacuum deposited onto a nominally 200 nm thick MCTS and then annealed. After deposition and annealing, a highly oriented crystalline structure is formed: its aspect ratio is large, with a controllable length of about 0.5 microns to 2 microns, a width of about 0.03 microns to 0.05 microns, an area density of about 30 whiskers per square micron, and the orientation of the structure is basically perpendicular to the substrate below it.
[0099] Comparative Example A
[0100] Nanostructured thin film (NSTF) catalyst layers were prepared by sequentially sputtering a catalyst film onto a microstructured whisker layer using a DC-magnetron sputtering process, Preparation Example A. A vacuum sputtering deposition system was used with a typical Ar sputtering gas pressure of about 3.3 mTorr (0.44 Pa) and a 5 inch × 15 inch (12.7 cm × 38.1 cm) rectangular Pt sputtering target. The system base pressure was typically 2.5 × 10 -5 Torr (0.0033 Pa), the background gas usually measured is water vapor. The coating is deposited by using ultra-high purity Ar as the sputtering gas.
[0101] A single Pt layer with an in-plane equivalent thickness of about 0.09 nm was first deposited from a pure Pt target onto the whiskers on MCTS. The Pt deposition process was repeated 50 times. The resulting deposit consisted of a single continuous Pt film with an overall continuous Pt in-plane equivalent thickness of about 4.7 nm, summarized in Table 1 below.
[0102] Table 1
[0103]
[0104] The areal Pt loading of the Pt layer was determined by multiplying the planar equivalent thickness by the density of the layer. The areal Pt loading of Comparative Example A, summarized in Table 2 below, was calculated by multiplying 4.7 nm by the Pt density of 2.145 μg / nm. 3 Determined to be 10 μg / cm 2 Comparative Example A contains no Ni, Ta or Ir, and has a Pt mole fraction of 1.00.
[0105] Table 2
[0106]
[0107] Metal is deposited onto an MCTS substrate coated with an NSTF support having an inherent roughness. The thickness of the metal film on the support is thinner than the equivalent thickness on the plane by the overall support factor and the substrate roughness factor. It is estimated that the NSTF support can provide 10 cm 2 Surface area / cm 2 planar area, and MCTS provides an additional 1.4cm 2 surface area, so the total surface area is 14cm 2 . Distributed in 14cm 2 / cm 2 The 4.7 nm plane equivalent thickness on the substrate is about 0.33 nm. The metal thickness on the support of Comparative Example A is summarized in Table 3 below.
[0108] Table 3
[0109]
[0110] The bulk composition of the representative area of the electrocatalyst was analyzed using X-ray fluorescence spectrometry (XRF). Representative catalyst samples were evaluated using a wavelength dispersive X-ray fluorescence spectrometer (purchased from Rigaku Corporation, Tokyo, Japan under the trade name "PRIMUS II" on MCTS), and the fluorescence spectrometer was equipped with a rhodium (Rh) X-ray source, a vacuum atmosphere environment, and a measurement area of 20-mm diameter. Each sample was analyzed three times to obtain the mean and standard deviation of the measured Pt, Ni, Ta, and Ir signal intensities, and the mean and standard deviation were proportional to the load. The Pt, Ni, Ta, and Ir loads of the electrocatalyst were determined by comparing their measured XRF intensities with the XRF intensities obtained with standard NSTF electrocatalysts containing Pt, Ni, Ta, and Ir with known area loads. The composition of the catalyst was calculated based on the Pt, Ni, Ta, and Ir loads determined by XRF. The loads and composition information of Comparative Example A are provided in Table 4 below. Comparative Example A contains 13.6 micrograms / cm 2 of Pt and contains no measurable Ta, Ni or Ir.
[0111] Table 4
[0112]
[0113] Next, the electrochemical performance of the catalysts was evaluated by assembling into a membrane electrode assembly (MEA) and using the catalysts as fuel cell cathodes, as described below. Typically, at least 2 MEAs were fabricated for each catalyst type, evaluated, and the average values reported.
[0114] The Comparative Example A catalyst and NSTF PtCoMn coated anode catalyst whiskers (0.05 mg) on MCTS were then laminated using a laminator (available from ChemInstruments, Inc., West Chester Township, OH, under the trade designation “HL-101”). Pt / cm 2 , Pt 69 Co 28Mn3) was transferred to either side of a 24 micron thick proton exchange membrane (obtained from 3M Company, St. Paul, Minnesota, USA under the trade designation "3M PFSA 825EW" (neat)) to form a catalyst coated membrane (CCM). The three-layer stack was manually fed into a laminator using hot rollers at 270°F (132°C), 150 psi (1.03 MPa) roll gap, and rotated at a speed equivalent to 0.5 fpm (0.25 cm / s). The MCTS layer was peeled off immediately after lamination, leaving the catalyst coated whiskers embedded on either side of the PEM. The CCM was mounted with identical gas diffusion layers (obtained from 3M Company under the trade designation "3M 2979 GASDIFFUSION LAYERS") on the anode and cathode, at 50 cm 2 Active area test cell (trade name "50CM 2 The "CELL HARDWARE" was obtained from Fuel Cell Technologies, Inc., Albuquerque, NM) with a quad serpentine flow field, and the gasket was selected to compress the gas diffusion layer by 10%. The comparative example A catalyst was evaluated as a fuel cell cathode.
[0115] After assembly, the test cell was connected to a test station (purchased from Fuel Cell Technologies, Inc. under the trade name "SINGLE FUEL CELL TEST STATION"). The MEA was then operated under a conditioning scheme for about 40 hours to achieve significant steady-state performance. The scheme consists of repeated cycles of operating and shut-down phases, each lasting about 40 minutes and 45 minutes, respectively. During the operating phase, the MEA was operated at 75°C cell temperature, 70°C dew point, 101 / 101 kPaA of H2 / air, with constant flow rates of H2 and air of 800 standard cubic centimeters per minute (sccm) and 1800 standard cubic centimeters per minute, respectively. During the 40-minute operating phase, the cell voltage alternated between 5-minute long polarization periods between 0.85V and 0.25V, and maintained a 5-minute long potential at 0.40V. During the 45 min shutdown phase, the cell potential was set to the open circuit voltage, the flow of H2 and air to the cell was stopped, and the cell temperature was cooled to room temperature while liquid water was injected into the anode and cathode cell inlets at 0.26 g / min and 0.40 g / min, respectively.
[0116] After conditioning the MEA, the electrocatalysts were characterized for relevant beginning of life (BOL) characteristics including catalyst activity, surface area, and operating performance under relevant H2 / air test conditions, as described below.
[0117] The absolute activity of the oxygen reduction reaction (ORR) at the cathode was measured at 900 mV for 1200 s relative to a 100% H2 reference electrode / counter electrode using saturated H2 / O2 at 150 kPaA and 80°C cell temperature. ORR absolute activity (A / cm 2 or mA / cm 2 ) is obtained by adding the current density measured after a holding time of 1050 s to the electron short circuit and hydrogen crossover current densities estimated from the 2 mV / s cyclic voltammogram measured with N2 added to the working electrode instead of O2. The corrected ORR absolute activity (A / cm 2 平面 ) divided by the cathode Pt area loading (mg / cm 2 ) to obtain Pt mass activity (A / mg Pt ), or by dividing the corrected ORR absolute activity by the cathode total platinum group metal (PGM) area loading to obtain the PGM mass activity (A / mg PGM ), thereby calculating the electrocatalyst mass activity, which is a measure of the catalyst activity per unit of precious metal content. The PGM mass activity of Comparative Example A is 0.14 A / mg PGM , reported in Table 5 below.
[0118] Table 5
[0119] Example Mass Activity Specific area Specific activity <![CDATA[A / mg PGM ]]> <![CDATA[m 2 PGM / g PGM ]]> <![CDATA[mA / cm 2 PGM ]]> Comparative Example A 0.14 10.4 1.35 Comparative Example B 0.16 13.2 1.23 Comparative Example C 0.16 11.4 1.37 Comparative Example D 0.15 9.5 1.61 Comparative Example E 0.16 8.0 2.01 Example 1 0.01 0.3 3.05 Example 2 0.09 3.2 2.46 Example 3 0.20 12.2 1.63 Example 4 0.19 12.6 1.50 Example 5 0.27 14.8 1.84 Example 6 0.21 13.0 1.62 Example 7 0.16 11.4 1.45 Example 8 0.00 0.2 0.00 Example 9 0.03 0.7 4.79 Example 10 0.21 15.1 1.41 Embodiment 11 0.20 15.4 1.31 Example 12 0.25 11.4 2.23 Example 13 0.36 20.7 1.76 Embodiment 14 0.29 19.3 1.51 Embodiment 15 0.25 15.7 1.61 Example 16 0.22 19.1 1.14 Embodiment 17 0.23 17.9 1.29 Embodiment 18 0.16 15.4 1.05
[0120] The surface enhancement factor (SEF, m) of the cathode catalyst was measured by cyclic voltammetry (100 mV / s, 0.65 V–0.85 V, average of 100 scans) at a saturated H2 / N2 pressure of 101 kPaA and a cell temperature of 70 °C. 2 PGM / m 2 平面 or similar cm 2 PGM / cm 2 平面 By taking the integral of the oxidation wave and the reduction wave, hydrogen underpotential deposition (H UPD ) Charge (microC / cm 2 平面 ) and divide it by 220 microC / cm 2 Pt To estimate SEF, we can use -SEF(m 2 PGM / m 2 平面 ) divided by the area PGM load (g PGM / m 2 平面 ), calculate the specific surface area of the electrocatalyst (m2 PGM / g PGM ), which is a measure of the dispersion of the catalyst. The specific area of Comparative Example A is 10.4 m 2 PGM / g PGM , reported in Table 5 above.
[0121] The corrected ORR absolute activity (A / cm 2 平面 ) divided by SEF (cm 2 PGM / cm 2 平面 ) to obtain (A / cm 2 PGM- ) or when converting the unit to mA / cm 2 PGM (A / cm 2 ) was multiplied by 1000 mA / A) to calculate the oxygen reduction specific activity of the cathode catalyst. The specific activity of Comparative Example A was 1.35 mA / cm 2 PGM , summarized in Table 5 above.
[0122] Comparative Example BE
[0123] Comparative Examples BE were prepared and characterized as described for Comparative Example A, except that the Pt deposition process was modified to provide a Pt areal loading of 23.8 μg / cm 2 , 27.0 μg / cm 2 , 54.2 μg / cm 2 and 98.1 μg / cm 2 The results are provided in Table 5 above.
[0124] Example 1
[0125] The Example 1 catalyst was prepared and characterized as described for Comparative Example A, except that a layer of tantalum was deposited prior to depositing Pt, the Pt deposition conditions were modified to vary the Pt loading, and the catalyst was thermally annealed prior to assembly into a membrane electrode assembly.
[0126] The NSTF catalyst layer was prepared by sequentially sputtering a catalyst film onto a microstructured whisker layer using a DC-magnetron sputtering process, Preparation Example A. A vacuum sputtering deposition system was used with a typical Ar sputtering gas pressure of about 3.3 mTorr (0.44 Pa) and 5 inch × 15 inch (12.7 cm × 38.1 cm) rectangular Pt and Ta sputtering targets. The system base pressure was typically 2.5 × 10 -5Torr (0.0033 Pa), the background gas usually measured is water vapor. The coating is deposited by using ultra-high purity Ar as the sputtering gas.
[0127] First, a single Ta layer with a planar equivalent thickness of about 0.5 nm was deposited from a pure Ta target onto the whiskers on MCTS. Ten Ta deposition processes were performed to obtain a Ta layer with a thickness of about 8 μg / cm 2 The area Ta loading, the Ta in-plane equivalent thickness of 4.9 nm, and the Ta thickness on the microstructured whiskers were about 0.0.35 nm. Next, a single Pt layer with an in-plane equivalent thickness of 0.46 nm was deposited. Five Pt deposition processes were performed to obtain about 10 μg / cm 2 The results show that the Pt loading on the microstructured whiskers was 0.17 nm (less than a Pt monolayer) and an areal Pt loading of 2.3 nm, a Pt plane equivalent thickness of 2.3 nm, and a Pt thickness on the microstructured whiskers of about 0.17 nm (less than a Pt monolayer).
[0128] After deposition, the electrocatalyst on MCTS was placed in a quartz tube furnace (purchased from Thermo Electron Corporation, Waltham, MA, under the trade name "LINDBERG BLUE M") and heated to 340°C under flowing H2. After about 20 minutes of temperature ramp, the catalyst was annealed at the above temperature for about 0.5 hours and then cooled to room temperature over a period of about 3 hours. After cooling to room temperature, the tube furnace was purged with nitrogen for about 15 minutes to remove any residual H2, after which the catalyst on the substrate was removed from the furnace. After annealing, the catalyst was assembled into a membrane electrode assembly and characterized as described for Comparative Example A. The results are provided in Table 5 above.
[0129] Embodiment 2-7
[0130] Examples 2 to 7 were prepared and characterized as described for Example 1, except that the Pt deposition process was modified so that the Pt area loading was approximately 10 μg / cm 2 , 15 μg / cm 2 , 20 μg / cm 2 , 40 μg / cm 2 , 50 μg / cm 2 and 78 μg / cm 2 , and were further characterized as described below. The results are provided in Table 5 above.
[0131] After fuel cell characterization was completed, the Example 2 catalyst was subjected to transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS) characterization. The Example 4 catalyst was subjected to TEM and EDS characterization after deposition of the catalyst metal onto the microstructured whiskers, after thermal annealing of the catalyst, and after fuel cell characterization. The Pt:Ta atomic ratios are summarized in Table 6 below. The Pt:Ta atomic ratio of Example 2 was 1.09. The Pt:Ta atomic ratios of the Example 4 catalyst after deposition, after annealing, and after fuel cell testing ranged between 2.17 and 2.27.
[0132] Table 6
[0133] Example state Pt:Ta atomic ratio Example 2 After the fuel cell test 1.09 Example 4 After deposition 2.17 Example 4 After annealing 2.22 Example 4 After the fuel cell test 2.27
[0134] Examples 2 and 4-7 were characterized by X-ray diffraction (XRD) to determine the apparent crystallite size and face-centered cubic (FCC) lattice parameters of the catalysts, which are summarized in Table 7 below.
[0135] Table 7
[0136]
[0137] The catalysts were XRD characterized after deposition and after annealing. After deposition, the apparent grain size of Examples 5-7 was in the range of 5.9 nm to 7.7 nm, and the FCC lattice parameter was in the range of 0.395 nm to 0.393 nm. After annealing, the apparent grain size of Examples 4-7 was in the range of 5.0 nm to 9.3 nm, and the FCC lattice parameter was in the range of 0.395 nm to 0.392 nm. No crystalline phase was detected in the Example 2 catalyst.
[0138] Examples 2 and 4-7 were further characterized by X-ray photoelectron spectroscopy (XPS) to determine the relative elemental concentrations near the catalyst surface. Table 8 below summarizes the relative atomic % of C, O, Pt, and Ta.
[0139] Table 8
[0140]
[0141] After deposition, the relative C concentration is in the range of 30.9 atomic % to 52.1 atomic %, the relative O concentration is in the range of 1.2 atomic % to 7.4 atomic %, the relative Pt concentration is in the range of 30.9 atomic % to 67.8 atomic %, and the relative Ta concentration is in the range of 0.0 to 19.5 atomic %. After annealing, the relative C concentration is in the range of 63.5 atomic % to 83.8 atomic %, the relative O concentration is in the range of 1.1 atomic % to 3.1 atomic %, the relative Pt concentration is in the range of 8.9 atomic % to 35.2 atomic %, and the relative Ta concentration is in the range of 0.1 atomic % to 4.9 atomic %.
[0142] Embodiment 8-11
[0143] Examples 8-11 were prepared and characterized as described for Example 1, except that the Ta and Pt deposition processes were modified so that the Ta and Pt areal loadings were different from those of Example 1, and Example 8 was additionally characterized as described below. The Ta areal loadings of Examples 8-11 were approximately 33 μg / cm 2 The Pt area loadings of Examples 8, 9, 10, and 11 were about 10 μg / cm 2 , 20 μg / cm 2 , 35 μg / cm 2 and 50 μg / cm 2 The results for Examples 8-11 are provided in Table 5 above. Additionally, the Example 8 catalyst was characterized by XRD and XPS as described above for Example 2, and the results for the Example 8 catalyst are provided in Tables 5, 7, and 8 above.
[0144] Example 12
[0145] Example 12 was prepared and characterized as described for Example 1, except that the Pt deposition conditions were modified to produce different Pt areal loadings, and Ni was also deposited.
[0146] The NSTF catalyst layer was prepared by sequentially sputtering a catalyst film onto a microstructured whisker layer using a DC-magnetron sputtering process, Preparation Example A. A vacuum sputtering deposition system was used with a typical Ar sputtering gas pressure of about 3.3 mTorr (0.44 Pa) and 5 inch × 15 inch (12.7 cm × 38.1 cm) rectangular Pt, Ta, and Ni sputtering targets. The system base pressure was typically 2.5 × 10 -5 Torr (0.0033 Pa), the background gas usually measured is water vapor. The coating is deposited by using ultra-high purity Ar as the sputtering gas.
[0147] First, the target area was loaded with 0.8 μg / cm 2A single Ta layer of 100 μg / cm2 was deposited from a pure Ta target onto the whiskers on MCTS. The Ta deposition process was performed 10 times to obtain a Ta content of approximately 8 μg / cm2. 2 Next, the target area loading was 1.0 μg / cm 2 Next, a single Pt layer with a targeted area loading of 0.5 μg / cm 2 The alternating Pt and Ni deposition process was performed 10 times to obtain about 10 μg Pt / cm 2 and 5 μg Ni / cm 2 The catalyst was annealed after deposition and characterized as described above for Example 1. The results are provided in Table 5 above.
[0148] Examples 13-15
[0149] Examples 13-15 were prepared and characterized as described for Example 8, except that the Pt and Ni deposition conditions were modified to produce different Pt and Ni loadings. The Pt loadings for Examples 13, 14, and 15 were 20 μg / cm 2 , 30 μg / cm 2 and 50 μg / cm 2 , and the Ni loading was 10 μg / cm 2 , 15 μg / cm 2 and 25 μg / cm 2 After deposition, the catalysts of Examples 13-15 were annealed and characterized as described for Example 1. The results are provided in Table 5 above.
[0150] Example 16
[0151] Example 16 was prepared and characterized as described for Example 1, except that a Tr layer was deposited onto the Ta layer prior to Pt deposition.
[0152] The NSTF catalyst layer was prepared by sequentially sputtering a catalyst film onto a microstructured whisker layer using a DC-magnetron sputtering process, Preparation Example A. A vacuum sputtering deposition system was used with a typical Ar sputtering gas pressure of about 3.3 mTorr (0.44 Pa) and 5 inch × 15 inch (12.7 cm × 38.1 cm) rectangular Pt, Ta, and Ir sputtering targets. The system base pressure was typically 2.5 × 10 -5 Torr (0.0033 Pa), the background gas usually measured is water vapor. The coating is deposited by using ultra-high purity Ar as the sputtering gas.
[0153] First, the target area was loaded with 0.8 μg / cm 2A single Ta layer of 100 μg / cm2 was deposited from a pure Ta target onto the whiskers on MCTS. The Ta deposition process was performed 10 times to obtain a Ta content of approximately 8 μg / cm2. 2 Next, a pure Ir target was deposited with a target area loading of 1.0 μg / cm 2 The Ir deposition process was repeated 5 times to obtain a single Ir layer of about 5 μg / cm 2 Next, the target area loading was 1.0 μg / cm 2 The Pt deposition process was performed 10 times to obtain a single Pt layer of about 10 μg / cm 2 After deposition, the Example 16 catalyst was annealed and characterized as described above for Example 1. The results are provided in Table 5 above.
[0154] Examples 17-18
[0155] Examples 17-18 were prepared and characterized as described for Example 16, except that the Ir deposition conditions were modified to produce different Ir loadings. The Ir loadings for Examples 17 and 18 were 10 μg / cm 2 and 15 μg / cm 2 The results are provided in Table 5 above.
[0156] Figure 3 Example 1-7 (with 8 μg / cm 2 Various Pt loadings on a fixed loading Ta underlayer), Examples 8-11 (with 33 μg / cm 2 Figure 2 is a graph of mass activity as a function of areal PGM loading for Examples AE (various Pt loadings on a fixed loaded Ta pad) and Comparative Examples AE (various Pt loadings without a pad). The mass activity of Comparative Examples AE ranges from 0.14 A / mg to 0.16 A / mg. The mass activity of Examples 1-12 ranges from 0.01 A / mg to 0.27 A / mg and depends on the Pt and Ta areal loadings. Over a similar range of areal PGM loadings, the mass activity of Examples 3-6 and 10-11 exceeds that of the Comparative Examples. Without being bound by theory, the mass activity depends on the Pt:Ta atomic ratio and Pt thickness, and higher mass activity may occur for catalysts within the optimal Pt:Ta atomic ratio and Pt thickness range.
[0157] Figure 4 Graph showing the specific activity of Examples 1-7, Examples 8-11 and Comparative Examples AE as a function of area PGM. The specific activity of Comparative Example AE is 1.35 mA / cm 2 Up to 2.01mA / cm 2The specific activity of Examples 1-7 is within the range of 1.45 mA / cm 2 Up to 3.05mA / cm 2 and the specific activities of Examples 8-11 were in the range of 0.00 to 4.79 mA / cm 2 In the range of similar area PGM loading range, the specific activities of Examples 1-5 and 9 are higher than the specific activities of the Comparative Examples. The specific activity of the Pt catalyst may depend on the Pt-Pt bond spacing, and without being bound by theory, the presence of the Ta underlayer may affect the Pt-Pt bond spacing at the Pt surface.
[0158] Figure 5 Graph of mass activity as a function of areal PGM loading for Examples 12-15 and Comparative Examples AE. Examples 12-15 include a PtNi surface layer on a Ta underlayer. The mass activities of Comparative Examples AE range from 0.14 A / mg to 0.16 A / mg, and the mass activities of Examples 12-15 range from 0.25 A / mg to 0.36 A / mg, which are higher than the Comparative Examples without a Ta underlayer.
[0159] Figure 6 Graphs of specific surface area as a function of areal PGM loading for Examples 1-7, Examples 16-18, and Comparative Examples AE. Examples 16-18 include an Ir layer between the Pt surface layer and the Ta underlayer. Comparative Examples AE have a specific surface area of 8.0 m 2 / g to 13.2m 2 The specific area of Examples 1-7 is within the range of 0.3 m 2 / g to 14.8m 2 / g, and the specific area of Examples 16-18 is 15.4 m 2 / g to 19.1m 2 / g range. The specific area of Examples 1-7 and 16-18 depends on the Pt, Ta and Ir area loadings. At the same PGM area loading, the specific area of Examples 16-18 including an Ir layer between the Pt layer and the Ta layer is higher than that of Examples 1-7 without an Ir layer between the Pt layer and the Ta layer. Without being bound by theory, the specific area may depend on the Pt:Ta atomic ratio, the Pt thickness, and the Ir thickness, and for a given Pt area loading, the presence of an Ir layer between the Pt layer and the Ta layer may produce a thinner Pt thickness due to the increased adhesion of Pt to the Ir layer compared to the adhesion of Pt to the Ta layer.
[0160] Table 9 below summarizes the percent increase in specific area for Examples 1-11 and Examples 16-18 relative to Comparative Examples AE at the same catalyst thickness on a whisker support.
[0161] Table 9
[0162]
[0163] The comparative example data were not available at the exact thickness on the support as in the examples. Using the comparative example AE data, the specific surface area at the specific thickness of examples 1-11 and examples 16-18 was estimated using linear interpolation. For example, the Pt+Ta thickness on the support of example 5 was 1.68nm, and the measured specific area was 14.8m 2 The Pt thicknesses of Comparative Examples D and E (not containing Ta) are 1.67 and 3.33, respectively, and the associated specific areas are 9.5 m 2 / g and 8.0m 2 Using linear interpolation, the estimated specific area of the comparative example at a thickness of 1.68 nm was estimated to be 9.5 m 2 / g. The specific area of Example 5 is 56% higher than the estimated value of Pt alone at the same thickness on the support ((14.8–9.5) / 9.5*100%). Similar analysis was performed on the data of Comparative Examples AE and Examples 1-11 and Examples 16-18. Based on thickness, the specific area of the data of Examples 1-11 ranged from 97% lower to 88% higher than that of Comparative Examples AE. The specific areas of Examples 16-18 ranged from 49% to 67% higher than those of Comparative Examples AE. The increase in specific area of the examples depends on the Pt thickness, Ta thickness, Pt:Ta atomic ratio, and the presence of an Ir layer between the Pt layer and the Ta layer.
[0164] Figure 7 is a graph of relative O content as a function of relative Ta content as determined by XPS analysis of the catalysts of Examples 2 and 4-8 in the as-deposited and annealed states and listed above in Table 8. The relative Ta and O contents are correlated with each other, indicating that the oxygen present is primarily associated with the tantalum and that the tantalum is at least partially oxidized.
[0165] Figure 8 and Fig. 9 TEM micrographs of Example 2 catalyst on microstructured whiskers after catalyst deposition and after fuel cell characterization, respectively. After deposition, Pt consists of a coating of nanoscale grains on the Ta layer. After fuel cell characterization, Pt consists of discontinuous islands on the Ta pad, and Pt is more condensed than after deposition, indicating that Pt has dewetted from the Ta pad. Fig.10 and Fig.11TEM micrographs of Example 4 catalyst on microstructured whiskers after catalyst deposition and after fuel cell characterization, respectively. After fuel cell characterization, the Pt consists of a largely continuous coating on the Ta underlayer, and the Pt coating after fuel cell characterization is much less agglomerated than Example 2.
[0166] like Figure 7 As shown and discussed above, Ta can be oxidized. Oxidized Ta has a lower conductivity than metallic Ta. Without being bound by theory, it is believed that Pt islands that are not in contact with other Pt islands and on a Ta layer with insufficient conductivity may not be used for electrochemical reactions, and the overall mass activity of the catalyst will be reduced. Compared with Example 2, the less condensed structure of the Pt coating of Example 4 can result in a higher mass activity of Example 4 than Example 2.
[0167] Fig.12 is a TEM micrograph of the Example 4 catalyst on microstructured whiskers after fuel cell testing. Fig.13 It is shown as Fig.12 EDS maps of Pt and Ta distribution over the same area shown. Fig.14 is an EDS map over the same area showing only Ta, and Fig.15 It is an EDS diagram showing only Pt. The surface of the catalyst is rich in Pt and on top of a Ta-rich layer, which itself is on a whisker support. After the fuel cell test, the layered structure produced during deposition was maintained. EDS is also used to determine the Pt:Ta atomic ratio of Example 2 and 4 catalysts. The Example 2 catalyst was evaluated after the fuel cell test, while the Example 4 catalyst was evaluated in the just-deposited, annealed and fuel cell test states. Table 6 above shows the Pt:Ta atomic ratios of Examples 2 and 4 measured via EDS, which are 1.09 and 2.27, respectively, similar to the targeted Pt:Ta atomic ratios of 1.16 and 2.32 listed in Table 2 above. The Example 4 Pt:Ta ratio in the just-deposited state and annealed state is similar to the Pt:Ta atomic ratio after the fuel cell test, indicating the electrochemical stability of Ta.
[0168] Fig.16 Graph summarizing the XRD spectra of Examples 2 and 4-8 taken after deposition of the catalyst onto the support and after thermal annealing. XRD was used to evaluate the bulk crystal structure of the catalysts, which is listed in Table 7 above. Example 2 (per cm on tantalum) 2 No crystalline Pt features were detected in either the as-deposited or annealed state, indicating that the Pt present was either amorphous or the grain size was too small to be detected. 2(Example 4), Pt features were detected after annealing, with a grain size of 5.0 nm and a lattice constant of 0.395 nm, which is larger than the lattice constant of 0.392 nm of bulk Pt. 2 (Example 5) The grain size increases to 5.9 nm and 6.0 nm in the as-deposited and annealed states, and the lattice constants are 0.395 nm and 0.393 nm, respectively, which are still larger than the lattice constant of bulk Pt. As the loading is further increased to 50 μg / cm 2 and 78 μg / cm 2 , the grain size increases further, consistent with the increasing Pt thickness on the Tantalum layer, and the lattice parameter decreases towards the pure Pt value.
[0169] Foreseeable variations and modifications of the present disclosure will be apparent to those skilled in the art without departing from the scope and spirit of the present invention.The present invention should not be limited to the embodiments shown in this application for illustrative purposes.
Claims
1. A product, comprising: a nanostructured element comprising a microstructured whisker having an outer surface; and A catalyst on the outer surface, the catalyst comprising a Ta layer, the Ta layer having an outer layer, the outer layer having a Pt-containing layer directly thereon, wherein the average thickness of the Ta layer is in the range of 0.04 nm to 30 nm, wherein the average thickness of the Pt-containing layer is in the range of 0.04 nm to 50 nm, and wherein the Pt and the Ta are present in an atomic ratio in the range of 0.28:1 to 9.04:
1.
2. The article of claim 1, wherein the surface area of the catalyst is at least 20% greater than the surface area of the catalyst that would be present in the absence of the Ta layer.
3. The article of claim 1, wherein the catalyst further comprises at least one pair of alternating layers, wherein the first alternating layers comprise Ta, and wherein the second alternating layers comprise Pt.
4. A catalyst, comprising: a Ta layer having an outer layer, the outer layer having a Pt-containing layer thereon, wherein the Ta layer has an average thickness in the range of 0.04 nm to 30 nm, wherein the Pt-containing layer has an average thickness in the range of 0.04 nm to 50 nm, and wherein the Pt and the Ta are present in an atomic ratio in the range of 0.28:1 to 9.04:1, and A layer containing Ir, the layer containing Ir being present between the Ta layer and the Pt layer, and wherein an average thickness of the layer containing Ir is in a range of 0.04 nm to 50 nm. The catalyst according to claim 4 , wherein the atomic ratio of the Ta to the Ir is in the range of 0.01:1 to 100:
1.
6. The article of claim 1, wherein the layer comprising Pt comprises Pt grains having a FCC lattice constant in the range of 0.395 nm to 0.392 nm.
7. The article of claim 1, wherein the layer comprising Pt comprises Pt grains having a grain size in a range of 2 nm to 20 nm.
8. The article of claim 1, wherein the layer comprising Pt further comprises Ni.
9. The article of claim 8, wherein the atomic ratio of the Pt to the Ni is in the range of 0.5:1 to 5:
1.
10. A method for preparing a catalyst according to claim 4, the method comprising depositing the Ta layer, the Ir layer, the Pt-containing layer or a combination thereof via a deposition technique independently selected from sputtering, atomic layer deposition, metal organic chemical vapor deposition, molecular beam epitaxy, ion soft landing, thermal physical vapor deposition, electrospray ionization vacuum deposition and pulsed laser deposition.
11. The article of claim 1, wherein the Ta layer is directly on the microstructured whiskers.
12. The article of claim 1, wherein the microstructured whiskers are attached to a backing.
13. A method for preparing an article according to claim 1, the method comprising depositing the Ta layer, the Pt-containing layer or both via a deposition technique, wherein the deposition technique is independently selected from sputtering, atomic layer deposition, metal organic chemical vapor deposition, molecular beam epitaxy, ion soft landing, thermal physical vapor deposition, electrospray ionization vacuum deposition and pulsed laser deposition. 14 . The method of claim 13 , further comprising annealing at least one of the Ta layer or the Pt-containing layer.
15. The catalyst of claim 4, wherein the Pt-containing layer comprises Pt grains having a FCC lattice constant in the range of 0.395 nm to 0.392 nm.
16. The catalyst of claim 4, wherein the Pt-containing layer comprises Pt grains having a grain size in the range of 2 nm to 20 nm.
17. The catalyst of claim 4, wherein the layer comprising Pt further comprises Ni.
18. The catalyst according to claim 17, wherein the atomic ratio of the Pt to the Ni is in the range of 0.5:1 to 5:1.